1971
DOI: 10.4153/cmb-1971-066-9
|View full text |Cite
|
Sign up to set email alerts
|

Topological Spaces with a Unique Compatible Quasi-Uniformity

Abstract: In [ 2 ] P. Fletcher proved that a finite topological space has a unique compatible quasi-uniformity; C. Barnhill and P. Fletcher showed in [1] that a topological space (X, ), with finite, has a unique compatible quasiuniformity. In this note we give some necessary conditions for unique quasiuniformizability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…PROOF: It is well known that in a topological space that admits a unique quasiuniformity every interior-preserving open collection is finite ([5], Theorem 2.36) and as is observed in [5] p. 45, in order to establish the converse it suffices to show that a topological space in which every interior-preserving open collection is finite is a transitive space (see [5], Corollary 2.8 and [9], Corollary 3.5).…”
Section: Theorem: a Topological Space X Admits A Unique Quasi-uniformmentioning
confidence: 99%
See 2 more Smart Citations
“…PROOF: It is well known that in a topological space that admits a unique quasiuniformity every interior-preserving open collection is finite ([5], Theorem 2.36) and as is observed in [5] p. 45, in order to establish the converse it suffices to show that a topological space in which every interior-preserving open collection is finite is a transitive space (see [5], Corollary 2.8 and [9], Corollary 3.5).…”
Section: Theorem: a Topological Space X Admits A Unique Quasi-uniformmentioning
confidence: 99%
“…The first part of Problem B is answered negatively in [7]; in this note we answer the second part positively. Topological spaces that admit a unique quasi-uniformity are considered in [1][2][3][4][5][8][9][10]. Related questions are dealt with in [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. By Corollary 3.5 of [2] it is sufficient to show that <^Q is totally bounded. Hence the result will follow if we can show that for any g-cover # the number of distinct sets A^ (xeX) is finite.…”
mentioning
confidence: 99%
“…(Here we assume that D0 = X.) Such spaces are studied under the name upq spaces in [7,8] and in [3] it is observed that each uqp Hausdorff space is finite (compare also [1, Proposition 4]). Two simple countable examples of first-countable uqp 7 0 -spaces that are not hereditarily compact (see for example [9]) are provided in [4].…”
Section: Introductionmentioning
confidence: 99%